PERAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KESADARAN ANTIKORUPSI DI KALANGAN MAHASISWA - Sa’diyah, Rika; Shofiyah, Siti; Sofia, Evi (FIKRAH, 2025)
This study aims to analyze the effectiveness of Islamic Religious Education in increasing anticorruption awareness among students. The widespread corruption phenomenon in Indonesia shows the importance of character education from an early age, especially through religious education. Islamic Religious Education has great potential in shaping anti-corruption character in students. In addition, this study identifies several factors that affect the effectiveness of Islamic religious education, such as the quality of lecturers, a conducive learning environment, and student involvement in religious activities. With a descriptive qualitative method, data was collected through in-depth interviews, observations, and document analysis of student learning in the Islamic Religious Education course at the University of Muhammadiyah Jakarta. The results of the study show that Islamic Religious Education that integrates anti-corruption values is effective in forming students’ awareness of the dangers of corruption and the importance of personal integrity. The research also shows the importance of a more intensive curriculum in terms of anti-corruption materials to support the achievement of anti-corruption attitudes among students. The findings of this study also recommend that universities pay more attention to the quality of Islamic religious education and integrate anti-corruption values more systematically in all aspects of learning. In addition, further research is needed to measure the long-term impact of Islamic religious education in shaping anti-corruption character in university graduates. It is hoped that it can produce a young generation who has high integrity and is able to contribute to building a nation that is clean from corruption.